2007
DOI: 10.1016/j.vetmic.2006.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Highly pathogenic avian influenza H5N1 virus in cats and other carnivores

Abstract: The Asian lineage highly pathogenic avian influenza (HPAI) H5N1 virus is a known pathogen of birds. Only recently, the virus has been reported to cause sporadic fatal disease in carnivores, and its zoonotic potential has been dominating the popular media. Attention to felids was drawn by two outbreaks with high mortality in tigers, leopards and other exotic felids in Thailand. Subsequently, domestic cats were found naturally infected and experimentally susceptible to H5N1 virus. A high susceptibility of the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 29 publications
(64 reference statements)
0
54
0
1
Order By: Relevance
“…Experimental inoculation of cats with HPAI H7N7 and H5N1 viruses has shown that felids can support infection with avian influenza viruses (58,59). Furthermore, ferrets have been shown to support the replication of influenza viruses isolated from felids (60).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental inoculation of cats with HPAI H7N7 and H5N1 viruses has shown that felids can support infection with avian influenza viruses (58,59). Furthermore, ferrets have been shown to support the replication of influenza viruses isolated from felids (60).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is difficult to explain pancreatic colonization by LPAI viruses, which is a common finding in infected chickens and turkeys (9)(10)(11)(12)(13)(14). Previous studies have reported that certain IAVs can also cause pancreatitis in mammals following natural or experimental infection (15)(16)(17)(18). Recently, there have been reports of pancreatic damage in human cases associated with H1N1pdm influenza A virus infection, including both acute pancreatitis and the onset of type 1 diabetes (T1D) (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Since then the virus has spread across Asia to Russia, the Middle East, Europe, and Africa, causing deaths in wild aquatic birds (13,58,71,81), domestic ducks and chickens (29,39,43), dogs and cats (2,35,36,55,76), and 254 of 405 confirmed human cases as of 5 February 2009 according to the World Health Organization (http://www.who.int/csr/disease /avian_influenza/).…”
mentioning
confidence: 99%